(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The purpose of this research is to demonstrate the impact of deposit insurance to reduce banking risks, as banks in various countries of the world face a variety of risks that led to banking and financial crises that led to the failure and bankruptcy of many of its bank, which led to the banks to find quick and appropriate solutions to get rid of these difficulties These solutions include the use of bank deposit protection system for the many risks and sequences of crises that accompanied the Iraqi banking work of thefts, forgery, embezzlement and changing and unstable circumstances. The importance of studying the subject of research through the theoretical framework of banking risks as well as the framework of consideration In order to guarantee bank deposits, the study was an analytical study of the Iraqi banking sector.